A Criminological Review of Gambling Practices at the Pangkalan Brandan Police Station - Ginting, Tomi Elvisa; Isnaini, Isnaini; Rafiqi, Rafiqi (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to examine gambling crimes in the jurisdiction of the Pangkalan Brandan Police from a criminological perspective. This study uses a qualitative method with a descriptive approach. Data was obtained through interviews with police officers, community leaders, and gamblers, as well as analysis of legal documents and police reports. The results of the study show that the main factors that encourage gambling include economic pressure, permissive social environment, and culture that considers gambling as a tradition. In addition, weak law enforcement and limited police resources are also obstacles in eradicating gambling. In an effort to counteract, the Pangkalan Brandan Police implemented a repressive strategy through raids and control operations, as well as a preventive strategy through socialization and education to the community. However, the effectiveness of law enforcement is still limited due to changes in the modus operandi of perpetrators and lack of public participation in reporting gambling cases. From a criminological perspective, this study confirms that gambling is a complex social phenomenon and requires a holistic approach in dealing with it. Synergy is needed between law enforcement officials, local governments, and the community to create a more effective strategy in eradicating gamblingy.